A triple lens measurement of host–guest perceptions for sustainable gaze in tourism. Issue 6 (3rd June 2017) - Tasci, Asli D. A.; Severt, Denver
ABSTRACT: This paper investigates perception of self and others by hosts and guests, which may be critical for sustainability of a destination receiving tourists with different cultural backgrounds. Specifically, the study investigates self-perception of hosts and reciprocal perception between hosts and guests on several service personnel characteristics using importance and performance analysis. Thus, a triple lens of hosts' evaluation of self, hosts' evaluation of the guests, and hosts' evaluation by the guests is involved in a multi-cultural tourism experience context. Results report differences between the lenses, hosts' self-evaluation being harsher than guests' evaluation of hosts. Suggestions are provided for destination marketing and management organizations to design effective tourism experiences for both hosts and guests for a more sustainable gaze between hosts and guests.